Sistem Informasi Geografis Rumah Sakit di Kota Bandar Lampung Berbasis Web - Nurjoko Nurjoko (Institut Informatika dan Bisnis Darmajaya, 2018)
Bandar Lampung is a city with a total of 16 units of hospitals and 30 units of puskesmas. In fact the condition of information systems about health facilities, especially in the city of Bandar Lampung can not be accessed by the general public quickly, accurately and accurately, this is due to the absence of information systems about health facilities in Bandar Lampung city terinventarisasi in an online information system spatial-based, health facility mapping data is still manual and not computerized. In this research, the design of geographic information system is done by using Unified Software Development Process (USDP) which consists of 4 stages, namely Planning, Analysis, Desaign, and Implementation. Geographic Information System Website Health Facilities in Bandar Lampung city can help and facilitate people to find location and information related to hospital and health center in Bandar Lampung city by showing spatial data and non spatial data from hospital and puskesmas. This website can show you the route to the destination health facility from where the user is located.Keywords: Geographic Information System; Health Facilities; Unified Software Development Process (USDP)